Teaching of alphabetical writing in the PNLD evaluation criteria (1998-2016): What knowledge and skills were contemplated? (Práxis Educativa, 2021)
This article presents the results of a study that aimed to analyze the criteria for evaluating literacy books or collections, instituted between 1998 and 2016, within the scope of the Programa Nacional do Livro Didático – PNLD (National Program for Textbooks).The focus was on the knowledge and skills related to the alphabetical writing system contemplated in these criteria in the Textbook Guidelines. The results showed: the first two editions of the Program contained few criteria related to this teaching axis, while the following editions progressively presented a growth in the number and diversity of knowledges/abilities which were evaluated. It was concluded that, initially, there seemed to be a certain contribution from the Program to the “literacy disinvention” in Brazil, but since 2010, there has been a gradual quest for conciliation between the teaching of the alphabetic writing system and reading practices and production of texts of different written genres, in the perspective of literacy with texts.Keywords: Teaching of alphabetic writing. Literacy textbooks. Evaluation of textbooks. PNLD.